MANAJEMEN PENGELOLAAN KOLAM RENANG GRAND MAYASARI ESTATE - Chintya Ayu Nur Lathifah; Muhammad Rizel Alfikri; Natanael Eka Putra Kaluti; Heri Yusuf Muslihin; Wulan Nurlaela (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
Many people utilize swimming pools for exercise, recreation, entertainment, and, nowadays, pools have become a promising business venture. Swimming pools are commonly found in hotels, tourist attractions, and even in modern times, residential homes often come equipped with pool facilities. The Grand Mayasari Estate Swimming Pool is one such pool in Tasikmalaya that is increasingly popular among visitors. This pool is privately owned, and its management provides a comfortable environment for both exercise and recreation. The aim of this research is to understand the management of the Grand Mayasari Estate Swimming Pool, focusing on planning, implementation, evaluation, follow-up, owner and member difficulties, and member development. The research method employed is qualitative with a descriptive approach. Data collection involves observation and interviews. The obtained data reveals effective management, evidenced by thorough planning regarding human resources, facilities, and training programs. Evaluation involves digitalization pressure and customer involvement as steps to adapt to industry trends. Management follow-up illustrates awareness of the importance of a digital presence. Challenges such as customer reviews and identifying areas for improvement are addressed through collaboration between management, customers, and members.